2015
DOI: 10.1080/10286020.2015.1121853
|View full text |Cite
|
Sign up to set email alerts
|

Two new glycosides from Dryopteris fragrans with anti-inflammatory activities

Abstract: Phytochemical investigation on the aqueous extract from Dryopteris fragrans led to the isolation of one new chromone glycoside, frachromone C (1), and one new coumarin glycoside, dryofracoulin A (2), together with one known undulatoside A (3). Their structures were elucidated by a combination of 1D and 2D NMR, HRMS, and chemical analysis. Compounds 1-3 exhibited inhibition on nitric oxide production in lipopolysaccharide induced RAW 264.7 macrophages with their IC50 values of 45.8, 65.8, and 49.8 μM, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…D. fragrans has been used as folk medicine for treating arthritis and skin diseases such as psoriasis, dermatophytosis, and more [ 3 ]. Previous phytochemical investigations on this plant have led to the identification of terpenoids [ 4 ], phloroglucinols [ 5 ], glucosides [ 6 ], and other phenolic derivatives such as coumarin [ 3 ]. The earlier biological studies have shown that D. fragrans was a valuable medicinal plant resource with extensive biological activities including anti-cancer, anti-oxidation, insect repellent, anti-microbial, and anti-inflammation activities [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…D. fragrans has been used as folk medicine for treating arthritis and skin diseases such as psoriasis, dermatophytosis, and more [ 3 ]. Previous phytochemical investigations on this plant have led to the identification of terpenoids [ 4 ], phloroglucinols [ 5 ], glucosides [ 6 ], and other phenolic derivatives such as coumarin [ 3 ]. The earlier biological studies have shown that D. fragrans was a valuable medicinal plant resource with extensive biological activities including anti-cancer, anti-oxidation, insect repellent, anti-microbial, and anti-inflammation activities [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ]. The chemical components isolated from D. fragrans have exerted many biological effects [ 3 , 4 , 5 , 6 ]. In recent years, there have been many studies regarding the anticancer components of D. fragrans .…”
Section: Introductionmentioning
confidence: 99%
“…Earliert his year,anew chromone glycoside knowna sf rach-romoneC (33;F igure 21), isolatedf rom Dryopteris fragrans (L.) Schott,w as found to inhibit CNO production. [57] In another recentr esearch effort, ac hloride-substituted 2-(2-phenethyl)chromone 34 (GYF-17; Figure 21) showedi nhibitory activity toward CNO synthesis. [58] The results also showedt hat this inhibitory activity is due to the suppression of iNOS expression, with consequent decrementi nCNO production.…”
Section: Cno Production Inhibitorsmentioning
confidence: 98%